Spatially Resolved Kinematics in the Central 1 kpc of a Compact Star-forming Galaxy at z ∼ 2.3 from ALMA CO Observations - Barro, G.; Kriek, M.; Pérez-González, P. G.; Diaz-Santos, T.; Price, S. H.; Rujopakarn, W.; Pandya, V.; Koo, D. C.; Faber, S. M.; Dekel, A.; Primack, J. R.; Kocevski, D. D. (Astrophysical journal. Letters, 2017)
We present high spatial resolution (FWHM ∼ 0 14) observations of the CO(8-7) line in GDS-14876, a compact star-forming galaxy at z = 2.3 with a total stellar mass of log(M /M ) = 10.9. The spatially resolved velocity map of the inner r 1 kpc reveals a continuous velocity gradient consistent with the kinematics of a rotating disk with vrot(r = 1 kpc) = 163 5 km s−1 and vrot/ ∼ 2.5. The gas-to-stellar ratios estimated from CO(8-7) and the dust continuum emission span a broad range, and , but are nonetheless consistent given the uncertainties in the conversion factors. The dynamical modeling yields a dynamical mass of , which is lower, but still consistent with the baryonic mass, , if the smallest CO-based gas fraction is assumed. Despite a low, overall gas fraction, the small physical extent of the dense, star-forming gas probed by CO(8-7), ∼3× smaller than the stellar size, implies a strong relative concentration that increases the gas fraction up to in the central 1 kpc. Such a gas-rich center, coupled with a high star formation rate (SFR) ∼ 500 M yr−1, suggests that GDS-14876 is quickly assembling a dense stellar component (bulge) in a strong nuclear starburst. Assuming its gas reservoir is depleted without replenishment, GDS-14876 will quickly (tdepl ∼ 27 Myr) become a compact quiescent galaxy that could retain some fraction of the observed rotational support.